Niż demograficzny a jakość kształcenia – czy dydaktyka akademicka stoi w obliczu kryzysu? - Sujkowska-Sobisz, Katarzyna (Forum Lingwistyczne, 2014)
Population decline vs. quality of education. Is academic didactics facing a crisis? The study raises the problem of the functioning of the academic didactics against the backdrop of new reality, socio-economic changes, and mental changes observed in young people. Based on the previous findings concerning the crisis in the academic didactics, the author proposes a reorientation within the scope of the target group of the prospective students. In her opinion, there is a need for drawing attention to the group of mature people (40+) as candidates for studies in humanities. Key words: population decline, humanistic education, Polish studies, National Qualification Framework, quality of education<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />